Knowledge management for designing business workflows through semantic compositions of web services. (1st January 2012) - Valtolina, Stefano; Barricelli, Barbara Rita; Ariano, Fabio; Padula, Marco; Scala, Paolo Luigi
This paper presents a workflow management system called task management system (TMS) devoted to help end users to combine and integrate distributed tasks through visual composition strategies. The TMS is devoted to support human resources in performing their working activities and in exploiting their knowledge and expertise. The TMS network allows employees, who are experts of a specific domain, to design a workflow, to visually validate its execution and to execute it at use time. In particular, the paper describes how workflow designers use TMS to transform the task analysis documents prepared by domain experts into a description of the workflow. The retrieved components are web services that are available in remote or local repositories representing distributed knowledge bases of business tasks. The TMS offers transparent invocation methods for invoking services by means of a semantic discovery engine designed for exploiting a taxonomy of web services.